A Socio-Technical Exploration for Reducing & Mitigating the Risk of Retained Foreign Objects - Cromie, Samuel; Corrigan, Siobhan; Kay, Alison; O'Byrne, Katie; Mc Donald, Nicholas (My University, 2018)
A Retained Foreign Object (RFO) is a fairly infrequent but serious adverse event. An accurate rate of RFOs is difficult to establish due to underreporting but it has been estimated that incidences range between 1/1000 and 1/19,000 procedures. The cost of a RFO incident may be substantial and three-fold: (i) the cost to the patient of physical and/or psychological harm; (ii) the reputational cost to an institution and/or healthcare provider; and (iii) the financial cost to the taxpayer in the event of a legal claim. This Health Research Board-funded project aims to analyse and understand the problem of RFOs in surgical and maternity settings in Ireland and develop hospital-specific foreign object management processes and implementation roadmaps. This project will deploy an integrated evidence-based assessment methodology for social-technical modelling (Supply, Context, Organising, Process & Effects/ SCOPE Analysis Cube) and bow tie methodologies that focuses on managing the risks in effectively implementing and sustaining change. It comprises a multi-phase research approach that involves active and ongoing collaboration with clinical and other healthcare staff through each phase of the research. The specific objective of this paper is to present the methodological approach and outline the potential to produce generalisable results which could be applied to other health-related issues.
PUBLISHED
Keywords: Retained foreign objects; Patient safety; Human factors; Sociotechnical systems; Risk management; Multi-disciplinary approach; Process modelling; Identities in Transformation; Inclusive Society; HUMAN FACTORS; Patient Safety; RISK MANAGEMENT; multi-disciplinary; process modelling; retained foreign objects; sociotechnical systems; Other; Communication; Health